The Role of Family Influence, Digital Competence, and Attitudes in Shaping Student Engagement in Digital Learning Environments - Desmarianti, Rika; Wulandari, Bunga Ayu; Kurniati, Erisa (Program Magister Teknologi Pendidikan Universitas Jambi, 2025)
The rapid integration of digital tools into the learning environment has made it essential to understand the factors that support sustained student engagement. This study investigates how family digital experience, perceived digital competence, and attitudes toward technology contribute to student engagement at Sinar Bijaksana Guang Ming Secondary and Senior High School in Jambi. A quantitative method was employed using an online questionnaire distributed to 248 students, with 205 valid responses analyzed through Partial Least Squares Structural Equation Modelling (PLS-SEM). The results indicate that family digital experience significantly influences students’ attitudes toward technology (p = 0.000) and perceived digital competence (p = 0.012). Perceived digital competence (p = 0.000) and attitudes toward technology (p = 0.025) positively predict student engagement. However, the direct effect of family influence on student engagement was not significant (p = 0.111), suggesting that its contribution operates indirectly through attitudes and competence rather than as a direct determinant. These findings highlight that students’ attitudes toward technology are the strongest predictor of engagement, underscoring the importance of fostering positive perceptions of digital learning environments. The study emphasizes the combined role of family support, digital confidence, and attitudinal readiness in enhancing sustained engagement and suggests further exploration of school- and peer-related factors in future research.